A review of syntactic complexity studies in context of EFL/ESL Writing - Yang, Yang; Yap, Ngee Thai; Mohamad Ali, Afida (Human Resource Management Academic Research Society, 2022)

(untitled)
This paper reviews more than 60 research papers, articles, or book chapters on syntactic complexity in the context of EFL/ESL writing in the past two decades. Most of the papers are from journals indexed in Social Science Citation Index, Scopus, and Chinese Social Science Citation Index. Five strands of syntactic complexity studies in the context of EFL/ESL writing are concluded: syntactic complexity measurement indices and tools, the relationship between syntactic complexity and language proficiency, syntactic complexity developmental studies, comparative studies, and variables influencing syntactic complexity. Gaps in previous studies and future research focuses are analyzed and concluded: new indices from other syntactic perspectives should be considered and research on their validity and reliability should be done. For comparative studies, more attention should be given to comparing the writing of EFL/ESL learners with different backgrounds. For research on variables influencing syntactic complexity, the interactive effect of multiple variables needs to be investigated; if only one variable is examined, other variables should be controlled. Besides, in future syntactic complexity research, theoretical interpretation and theory building should be given more attention, and the observation period for longitudinal research should be extended. Finally, more qualitative studies are needed for in-depth investigation of specific syntactic perspectives, such as syntactic errors.